Surgical treatment of carcinoma of the oesophagus. - Dark, J F (1981)
Seven hundred and seventy-two patients suffering from carcinoma of the oesophagus and upper stomach were seen by two surgeons at the Manchester Regional Cardiothoracic Centre over a 15-year period. Five hundred and thirty-one patients had an operation, and of these, 449 had a resection. Throughout the period under review, the policy was to resect the primary tumour whenever possible. No emphasis was placed on extensive preoperative parenteral feeding. Adequate rather than radical resection was the aim of the surgery, but even if a curative operation was not possible, the primary was removed if at all possible. Gastric drainage in the immediate postoperative period by nasogastric tube or pyloroplasty was never used. A new classification of high or low tumours according to the level seen at oesophagoscopy is suggested; in 30 cases designated as "high", a planned resection was carried out using a bilateral thoracotomy, a method not previously described. The overall operative mortality was 9.2%. Of those having a resection it was 7.6%, and there were only three deaths in the last 120 resections. The predicted actuarial survival in this series of resections was 18% at five years and 12% at 10 years.